1986
DOI: 10.1021/j100280a086
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon gels from water-in-oil microemulsions

Abstract: A procedure is described that permits the transformation of hydrocarbon microemulsions into gels. This is obtained by cooling a previously heated isooctane solution of bis(2-ethylhexyl) sodium sulfosuccinate containing 10-20% of an aqueous gelatin solution. The final system is a homogeneous gel, whose consistency and physical properties vary depending upon the relative concentration of water and gelatin. These new hydrocarbon gels have been investigated with 'H NMR, circular dichroism, differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
79
0
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(85 citation statements)
references
References 0 publications
0
79
0
6
Order By: Relevance
“…The field of organogelators has attracted interest due to industrial applications in many areas such as cosmetics, polymers, and soft condensed matter with advanced functions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The process of these self-assembly-type gelators is driven by specific noncovalent intermolecular interactions. The physical gels formed are therefore thermoreversible.…”
Section: Introductionmentioning
confidence: 99%
“…The field of organogelators has attracted interest due to industrial applications in many areas such as cosmetics, polymers, and soft condensed matter with advanced functions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The process of these self-assembly-type gelators is driven by specific noncovalent intermolecular interactions. The physical gels formed are therefore thermoreversible.…”
Section: Introductionmentioning
confidence: 99%
“…The gel matrix formed by a gelling agent, such as gelatin, fully retains the surfactant, water and enzyme components and can be handled as an immobilized biocatalyst that facilitates the diffusion of non-polar substrates and products. The preparation of MBGs was first reported in 1986 [6][7][8] and subsequent spectroscopic investigations [9,10] have shown that the microemulsion structure is well preserved in the network of the gels, which are believed to contain a more or less bicontinuous phase that may co-exist with conventional w/o microemulsion droplets. MBGs containing immobilized lipase were applied for the preparative scale synthesis of miscellaneous esters and both regio-and stereoselectivity have been observed [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A formação do organo-gel foi primeiramente descrita em 1986, [15][16] e sua caracterização física/estrutural tem sido alvo de vários estudos [17][18][19][20][21] .…”
Section: Introductionunclassified